Quality of life of patients with 3D-printed arm prostheses in a rural area of Sierra Leone. Issue 7 (July 2021) - Sterkenburg, A.J.; Van der Stelt, M.; Koroma, A.R.; Van Gaalen, M.D.; Van der Pols, M.J.; Grobusch, M.P.; Slump, C.H.; Maal, T.J.J.; Brouwers, L.
Abstract: Introduction: In Sierra Leone, access to prostheses is limited due to absence of practical knowledge, materials, trained staff, and high cost. This paper investigates the impact of a 3D printed prosthesis on the health-related quality of life (HRQoL) in prosthesis recipients. Methods: Patients with upper extremity amputations were included in this case study from December 2018 until July 2019. Data on the HRQoL was gathered until April 2020 in Masanga Hospital, central rural Sierra Leone. At two follow-up moments the HRQoL was assessed by applying the standard EQ-5D-5L questionnaire. These two follow-up moments varied between one week and just over a year after receiving the prosthesis. A second patient questionnaire was used to assess prosthesis satisfaction. Results: Seven patients were included. The results of the EQ-5D-5L questionnaire show no deterioration of the HRQoL in any patient and the overall HRQoL increased by almost 20% compared to the null measurement. One patient was lost to follow up after the first re-visit. The responses to the second questionnaire indicated that patients are satisfied with the prosthesis and use it in various situations. Patients often mentioned they feel more included in society when wearing the prosthesis. One patient says wearing the prosthesis helped in accepting the amputation. As a result, enough self-confidence was experienced without the prosthesis and the patients stopped wearing the prosthesis. Discussion: The overall HRQoL in patients wearing a 3D-printed prosthesis increases compared to not wearing one. Assessing the HRQoL at regular intervals is important for the long-term follow-up and to safeguard sustainability and long-term success of this project. Nevertheless, defining the HRQoL is challenging due to cultural differences and misunderstandings. Therefore, the use of alternative questionnaires to define the HRQoL should be investigated. To improve and warrant long-term success, identifying long-term problems is important, and the second questionnaire accounts for this need. Highlights: 3D printing may increase the accessibility of prostheses in a rural area A 3D printed prosthesis increases the quality of life compared to no prosthesis People feel included in society when using a 3D printed prosthesis instead of none Long term follow up is necessary to safeguard the long-term success of this project Costs of a 3D printed prosthesis will not be more than costs of a conventional one Abstract : 3D printing; Prosthesis; Sierra Leone; Health related quality of life